Enhanced Triacylglycerol Production With Genetically Modified Trichosporon oleaginosus - Koivuranta, Kari; Castillo, Sandra; Jouhten, Paula; Ruohonen, Laura; Penttilä, Merja; Wiebe, Marilyn G. (Frontiers in Microbiology, 2018)
Mitochondrial pyruvate dehydrogenase (PDH) is important in the production of lipids in oleaginous yeast, but other yeast may bypass the mitochondria (PDH bypass), converting pyruvate in the cytosol to acetaldehyde, then acetate and acetyl CoA which is further converted to lipids. Using a metabolic model based on the oleaginous yeast Yarrowia lipolytica we found that introduction of this bypass to an oleaginous yeast should result in enhanced yield of triacylglycerol on substrate. Trichosporon oleaginosus (formerly Cryptococcus curvatus) is an oleaginous yeast which can produce triacylglycerols from both glucose and xylose. Based on the sequenced genome, it lacks at least one of the enzymes needed to complete the PDH bypass, acetaldehyde dehydrogenase, and may also be deficient in pyruvate decarboxylase and acetyl-CoA synthetase under production conditions. We introduced these genes to T. oleaginosus in various combinations and demonstrated that the yield of TAG on both glucose and xylose was improved, particularly at high C/N ratio. Expression of a phospholipid:diacyltransferase encoding gene in conjunction with the PDH bypass further enhanced lipid production. The yield of triacylglycerol on xylose (0.27 g g-1) in the engineered strain approached the theoretical maximum yield of 0.289 g g-1. Interestingly, triacylglycerol production was also enhanced compared to the control in some strains which were given only part of the bypass pathway, suggesting that these genes may contribute to alternative routes to cytoplasmic acetyl CoA. The metabolic model indicated that the improved yield of triacylglycerol on substrate in the PDH bypass was dependent on the production of NADPH by acetaldehyde dehydrogenase. NADPH for lipid synthesis is otherwise primarily supplied by the pentose phosphate pathway. This would contribute to the greater improvement of triacylglycerol production from xylose compared to that observed from glucose when the PDH bypass was introduced, since xylose enters metabolism through the non-oxidative part of the pentose phosphate pathway. Yield of triacylglycerol from xylose in the engineered strains (0.21 to 0.27 g g-1) was comparable to that obtained from glucose and the highest so far reported for lipid or TAG production from xylose.